2016
DOI: 10.2176/nmc.ra.2015-0296
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy for Malignant Brain Tumors

Abstract: Photodynamic therapy (PDT) using talaporfin sodium together with a semiconductor laser was approved in Japan in October 2003 as a less invasive therapy for early-stage lung cancer. The author believes that the principle of PDT would be applicable for controlling the invading front of malignant brain tumors and verified its efficacy through experiments using glioma cell lines and glioma xenograft models. An investigator-initiated clinical study was jointly conducted with Tokyo Women’s Medical University with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 26 publications
1
80
0
8
Order By: Relevance
“…Several studies have provided insights into mechanisms promoting accelerated neural differentiation and tissue regeneration (33,34). In complimentary clinical and experimental studies, documented imbalances of neuromediators found in denervated tissue are associated with conditions where delayed wound healing is common.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have provided insights into mechanisms promoting accelerated neural differentiation and tissue regeneration (33,34). In complimentary clinical and experimental studies, documented imbalances of neuromediators found in denervated tissue are associated with conditions where delayed wound healing is common.…”
Section: Discussionmentioning
confidence: 99%
“…Among its several advantages, worthy of note are the minimum systemic adverse effects due to its double selectivity (de Freitas et al, 2017). In the past decade, the DNA repair genes in astrocytoma 9 application of PDT to treat GBM has been investigated and proven to be a promising approach, both in vitro and in vivo (Chakrabarti et al, 2013;Akimoto, 2016). In fact, the Japanese health insurance coverage has introduced, since September 2013, the PDT as a new intraoperative therapy with an indication for malignant brain tumors (Akimoto, 2016).…”
Section: New Therapies and Future Prospectivementioning
confidence: 99%
“…Firstly, it helps the surgeon to locate the whole tumor through the fluorescence emission of the photosensitizers (Fluorescence Image Guided Surgical Resection), providing higher rates of complete resection (Eljamel, 2015). Secondly, PDT increases the success of tumor ablation by eliminating its roots while normal brain tissue is spared due to a preferable accumulation of PSs in tumor cells, improving progression-free and overall survival of patients (Akimoto, 2016). However, several variables were found among the studies, including light dose and delivery method, photosensitizer utilized, and sensitivity of different tumor types, evidencing the requirement of standardized clinical trials to effectively evaluate PDT as a treatment option for GBM patients (Quirk et al, 2015).…”
Section: New Therapies and Future Prospectivementioning
confidence: 99%
“…Its use for treatment of age-related macular degeneration (3)(4)(5), actinic keratosis (6,7), esophageal cancers (8,9), and non-small cell lung cancer (10,11) has been approved by the FDA. The use of PDT in pre-clinical studies and clinical trials for skin (12)(13)(14), bladder (15), prostate (16), brain (17,18), and head and neck cancers (19)(20)(21)(22), as well as malignant mesothelioma (23)(24)(25) and gynecologic disease (26) have been reported. In contrast with chemotherapy, PDT is a highly localized treatment technique that can spare healthy cells.…”
Section: Introductionmentioning
confidence: 99%